Perancangan Sistem Kasir Dan Laporan Keuangan Berbasis Web Pada Toko Andi Elektrik - Andi Arianto Limbong; Abdul Khaliq; Barany Fachri (Jurnal Nasional Teknologi Komputer, 2026)
The development of information technology is encouraging businesses to shift from manual to digital systems to improve the efficiency and accuracy of data management. Tokoh Andi Elektrik, which sells electrical equipment, still records transactions, inventory, and financial reports manually, potentially leading to recording errors, reporting delays, and the risk of data loss. This research aims to design and build a web-based cashier and financial reporting system capable of managing sales transactions, product data, inventory, catalogs, and generating financial reports automatically and in a structured manner. The system development method used is the Waterfall method, which includes requirements analysis, system design, implementation, testing, and maintenance. The system was developed using PHP, MySQL, HTML, CSS, and JavaScript and implemented in a localhost environment. The results show that the system can improve transaction process efficiency, simplify inventory management, and produce faster, more accurate, and more secure financial reports. With this system, it is hoped that Tokoh Andi Elektrik's operational management will be more effective and support optimal business decision-making.